Self-Responsibility: Transformations. (January 2019) - Maier, Robert
Self-responsibility is a concept of modern times; however, it has roots going back to ancient times. It points to the accountability of individuals for their actions. Therefore, it presupposes at least some degree of autonomy of the individual as a responsible member of the social fabric. That self-responsibility has changed significantly in modern times, and particularly during recent decades, is the main thesis of this article. In a first part, the concept of (self-)responsibility is examined briefly, and its different dimensions are pointed out. Recent transformations in the notion of self-responsibility are put forward as a hypothesis. Then the central part of this article addresses the question how welfare arrangements have been reorganized in recent decades as a result of the transformations in the concept of self-responsibility. Finally, I mention the main forms of resistance this new type of self-responsibility.